The Influence of Islamic Leadership and Islamic Work Ethic on Employee Performance with Emotional Intelligence as an Intervening Variable (Study of Employees of the Ministry of Religion in Central Java Province) - Al Jabar, Fawwaz Arif; Suharnomo, Suharnomo (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
The Ministry of Religion is responsible for administering various public services related to religion, such as organizing worship, religious education, community development, and hajj management. The quality of employee performance directly affects the effectiveness and quality of these services provided to the public. Therefore, it is crucial to improve the performance of employees within the Ministry of Religion of Central Java Province as it directly contributes to enhancing the quality of public services in the religious sector. Employee performance is influenced by factors such as Islamic leadership, Islamic work ethics, and emotional intelligence. This study aims to examine the impact of Islamic leadership style and Islamic work ethics on employee performance, with emotional intelligence acting as an intermediate variable. The research adopts a quantitative approach and gathers primary data from employees who identify as Muslims in the Ministry of Religion of Central Java Province, totaling 118 individuals. Data collection involves using a Likert scale questionnaire ranging from 1 to 7. Hypothesis testing utilizes an alternative Structural Equation Modeling (SEM) method called Partial Least Squares (PLS). The study's findings reveal that there is no direct effect of Islamic leadership style and Islamic work ethics on employee performance. However, Islamic leadership style and Islamic work ethics have a positive and significant influence on employees' emotional intelligence. Additionally, emotional intelligence has a positive and significant impact on employee performance. Emotional intelligence is validated as an intervening variable that mediates the influence of Islamic leadership and Islamic work ethics on employee performance